Der Imperativsatz im Slowakischen mit Blick auf andere westslawische Sprachen Syntax, Semantik und Pragmatik eines Satztyps - Späth, Andreas (Specimina philologiae Slavicae, 1996)
The aim of this work is to integrate the West Slavic languages ​​into grammar and language comparisons using modern grammatical approaches. This is done using the example of the imperative sentence in Slovak with a view to other West Slavic languages. This type of sentence is examined for its formal and content-related characteristics. At the same time, its communicative-pragmatic potential is derived and explained from the structural meaning of this mode verbi. The demarcation between the grammar and the pragmatics of the imperative theorem will play an important role here.